Transesophageal Echocardiogram-Guided Stent Placement in Superior Vena Cava Syndrome Secondary to Granulomatous Lung Disease: A Case Series and Literature Review. (November 2017) - Sun, Kaiwen; Batra, Rishi; Markin, Nicholas W.; Suh, Melissa; Pipinos, Iraklis I.; Roberts, Ellen K.; Mactaggart, Jason N.; Baxter, B. Timothy
Obstruction of the superior vena cava (SVC) is an uncommon, but potentially life-threatening condition due to likely development of edema in the head and neck and potential respiratory compromise. Less than half of those affected by SVC syndrome survive more than a year. Obstruction can be from neoplasms or secondary to benign disease. Treatment for most cases of symptomatic SVC syndrome involves placement of a stent to relieve the stenosis. Serious complications such as stent migration, pulmonary embolism, and cardiac tamponade can occur in 5% to 10% of cases, and inadequate imaging of the SVC–atrial junction by fluoroscopy contributes to these problems. The overlapping contrast in the atrium makes it difficult to precisely place the distal end of the stent, potentially allowing for embolization of the stent to occur. We present a case series of 3 patients wherein transesophageal echocardiography was used for guidance of stent placement in the SVC and significantly aided in placement.